2009
DOI: 10.1029/2009gl039468
|View full text |Cite
|
Sign up to set email alerts
|

Helium isotope variations in seafloor basalts from the Northwest Lau Backarc Basin: Mapping the influence of the Samoan hotspot

Abstract: New helium isotope results for seafloor basalts from the northern Lau Basin indicate that the signature of the Samoan hotpot has penetrated beneath the Rochambeau Rifts (RR) and the Northwest Lau Spreading Center (NWLSC) all the way to the Peggy Ridge (PR). Helium isotope ratios in 29 samples from the NWLSC – RR range from 10.9 to 28.1 Ra, all clearly higher than typical depleted mantle or MOR‐type values. Comparison with other helium results from the northern Lau Basin show the Samoan hotspot influence is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(126 citation statements)
references
References 27 publications
8
117
1
Order By: Relevance
“…It extends for at least 165 km more or less parallel to the Tonga Ridge, and approaches to within $40 km of the volcanic island of Ata in the Tofua Arc. In the northern basin, there is a short ridge segment north of PR called the Northern Lau Spreading Center (NLSC) and a three- Tables 1 and 2) are shown as red circles and other available 3 He/ 4 He data in the Lau Basin are shown as open circles (Poreda, 1985;Poreda and Craig, 1992;Poreda and Farley, 1992;Hilton et al, 1993;Honda et al, 1993;Bach and Niedermann, 1998;Lupton et al, 2009). Gray shade indicates areas shallower than 2000 m. (For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.)…”
Section: Geological Background and Samplesmentioning
confidence: 99%
“…It extends for at least 165 km more or less parallel to the Tonga Ridge, and approaches to within $40 km of the volcanic island of Ata in the Tofua Arc. In the northern basin, there is a short ridge segment north of PR called the Northern Lau Spreading Center (NLSC) and a three- Tables 1 and 2) are shown as red circles and other available 3 He/ 4 He data in the Lau Basin are shown as open circles (Poreda, 1985;Poreda and Craig, 1992;Poreda and Farley, 1992;Hilton et al, 1993;Honda et al, 1993;Bach and Niedermann, 1998;Lupton et al, 2009). Gray shade indicates areas shallower than 2000 m. (For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.)…”
Section: Geological Background and Samplesmentioning
confidence: 99%
“…One would expect the helium isotopic signature in the hydrothermal fluids to agree with that in the volcanic rocks, since the vent fluid helium is extracted from the volcanic rocks or magma by hydrothermal circulation. Lupton et al [2009] reported 17.8 R a for one basalt sample collected from the summit of Lobster Caldera, while two additional samples on the flanks of Lobster reported previously by Poreda and Craig [1992] measured 21.9 and 22.1 R a . Thus the helium endmember estimate of 18.7-19.3 R a from the plume measurements at Lobster Caldera is in reasonable agreement with the basalt results.…”
Section: End-member Helium Isotope Compositionsmentioning
confidence: 99%
“…Lupton et al [2009] demonstrated that these elevated helium isotope ratios are not confined to the RR, but extend southward along the NWLSC to the Peggy Ridge. In contrast to the NWLSC-RR, the spreading centers of the northeast Lau Basin have typical MOR-type helium isotope ratios [Poreda and Craig, 1992;Hilton et al, 1993;Honda et al, 1993;Lupton et al, 2009]. Thus these elevated 3 He/ 4 He ratios appear to be confined to the NWLSC-RR system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations